2012
DOI: 10.1210/en.2012-1316
|View full text |Cite
|
Sign up to set email alerts
|

The Androgen Metabolite, 5α-androstane-3β,17β-diol, Decreases Cytokine-Induced Cyclooxygenase-2, Vascular Cell Adhesion Molecule-1 Expression, and P-Glycoprotein Expression in Male Human Brain Microvascular Endothelial Cells

Abstract: P-glycoprotein (Pgp), a multiple drug resistance transporter expressed by vascular endothelial cells, is a key component of the blood-brain barrier and has been shown to increase after inflammation. The nonaromatizable androgen, dihydrotestosterone (DHT), decreases inflammatory markers in vascular smooth muscle cells, independent of androgen receptor (AR) stimulation. The principal metabolite of DHT, 5α-androstane-3β,17β-diol (3β-diol), activates estrogen receptor (ER)β and similarly decreases inflammatory mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 90 publications
2
30
0
Order By: Relevance
“…Both A-dione and A-diol have been shown to activate AR target genes [90], and A-diol has recently been shown to bind to ERβ [132]. Furthermore, A-diol exhibits anti-inflammatory properties in brain microglia and microvascular endothelial cells [132,170] although a PubMed search did not reveal any reports regarding vasoactive properties for Adiol in the cerebral circulation. Further metabolism of A-dione and A-diol results in the production of TEST which is then aromatized to E2.…”
Section: Androgen Biosynthesis In the Cerebrovasculaturementioning
confidence: 99%
See 4 more Smart Citations
“…Both A-dione and A-diol have been shown to activate AR target genes [90], and A-diol has recently been shown to bind to ERβ [132]. Furthermore, A-diol exhibits anti-inflammatory properties in brain microglia and microvascular endothelial cells [132,170] although a PubMed search did not reveal any reports regarding vasoactive properties for Adiol in the cerebral circulation. Further metabolism of A-dione and A-diol results in the production of TEST which is then aromatized to E2.…”
Section: Androgen Biosynthesis In the Cerebrovasculaturementioning
confidence: 99%
“…Unlike 3α-diol, 3β-diol cannot be converted back to DHT and undergoes biotransformation to inactive metabolites by the enzyme CYP7B1 [145,157]. We recently demonstrated that mRNAs for 3β-HSD, 3α-HSD, 17β-HSD, and CYP7B1 are present in human brain microvascular endothelial cells [170]. 3β-Diol is an intriguing endogenous androgen with evidence of having a physiological role in the brain and in the cerebrovasculature.…”
Section: Androgen Biosynthesis In the Cerebrovasculaturementioning
confidence: 99%
See 3 more Smart Citations